The chloride co-transporters, NKCC1 and KCC2, in experimental autoimmune encephalomyelitis (EAE). (6th March 2017) - Yousuf, Muhammad Saad; Zubkow, Kasia; Tenorio, Gustavo; Kerr, Bradley
Highlights: Mice with experimental autoimmune encephalomyelitis (EAE) exhibit mechanical hypersensitivity at onset of symptoms. Chloride co-transporters, NKCC1 and KCC2, are downregulated in the dorsal spinal cord with onset of EAE. NKCC1 levels are enhanced in the dorsal root ganglia at the same time point. Bumetanide treatment reverses changes in chloride co-transporters with no effect on mechanical hypersensitivity. Oligomeric KCC2 expression remains repressed with bumetanide treatment. Abstract: Patients with multiple sclerosis (MS) often complain of neuropathic pain. According to the Gate Control Theory of Pain, spinal networks of GABAergic inhibitory interneurons are important in modulating nociceptive inputs from the periphery. Na+–K+–2Cl− co-transporter 1 (NKCC1) and K+–Cl− co-transporter 2 (KCC2) generally dictate the tone of GABA/glycine inhibition by regulating intracellular chloride concentrations. In this study, we investigated the role of NKCC1 and KCC2 in neuropathic pain observed in the animal model, experimental autoimmune encephalomyelitis (EAE), a commonly used model to study the pathophysiology of MS. Quantitative real-time polymerase chain reactions (qRT-PCR) analysis revealed no change in NKCC1 mRNA transcripts in dorsal root ganglia throughout EAE disease course. However, NKCC1 and KCC2 mRNA levels in the dorsal spinal cord were significantly reduced at disease onset and peak only to recover by the chronic time point. Similarly, Western blot data revealed a significant downregulation of NKCC1 and KCC2 in the dorsal spinal cord at disease onset but an upregulation of NKCC1 protein in the dorsal root ganglia at this time point. Treatment with bumetanide, an NKCC inhibitor, had no effect on mechanical hypersensitivity seen in mice with EAE even though it reversed the changes in the levels of NKCC1 and KCC2. We noted that bumetanide treatment, while effective at reversing the changes in monomeric KCC2 levels was ineffective at reversing the changes in oligomeric KCC2 which remained repressed. These results indicate that mechanical hypersensitivity in EAE is not mediated by altered levels of NKCC1.